Efektivitas Model Pembelajaran Icare (Introduction, Conection, Application, Refllectio, Extention) Dalam Meningkatkan Keterampilan Berpikir Kreatif Siswa Kelas F SMAN 26 Bone: (The Effectiveness Of The Icare Learning Model (Introduction, Connection, Application, Reflection, Extention) In Improving Creative Thinking Skills In Class F Students Of Sman 26 Bone) - Hasni , Hasni; Nurmi, Nurmi; Adiansyah , Romi (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This research aims to prove the effectiveness of the ICARE Learning Model in Improving the Creative Thinking Skills of Class F Students at SMAN 26 Bone. This research is quantitative with a Nonequivalent Control research type with Design Group pre-test and post-test design type. The data processed is data on the population and sample of students, pre-test and post-test learning outcomes, and documentation. The data collection techniques used in this research were administering Creative Thinking skills questionnaires, learning outcomes tests (Pre-Test and Post-Test) and documentation. The results of descriptive analysis using a creative thinking ability questionnaire to describe students' creative thinking abilities showed that different scores in the 65-79 interval were categorised as good. In comparison, the 99 interval was categorised as very good, whereas the score was categorised as good. Next, the results of the inferential analysis were carried out using the SPSS Version 25 application. The results of the normality and homogeneity tests obtained normal and homogeneous data results. Meanwhile, hypothesis testing was carried out using Paired Sample Pre-test and Post-test and obtained a significant value smaller than 0.05, namely 0.000 where sig (2-tailed) <0.05. This proves that the ICARE Learning Model is improving the creative thinking skills of Class F students at SMAN 26 Bone. Abstrak. Penelitian ini bertujuan untuk membuktikan Keefektifan Model Pembelajaran ICARE dalam Meningkatkan Keterampilan Berpikir Kreatif Siswa Kelas F di SMAN 26 Bone. Penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian Nonequivalent Control dengan tipe desain pre-test and post-test Design Group. Data yang diolah adalah data populasi dan sampel siswa, hasil belajar pre test dan post test, dokumentasi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah pemberian angket keterampilan Berpikir Kreatif, tes hasil belajar (Pre-Test dan Post Test) dan dokumentasi. Hasil analisis deskriptif menggunakan angket kemampuan berpikir kreatif untuk mendeskripsikan kemampuan berpikir kreatif siswa menunjukkan bahwa skor yang berbeda pada interval 65-79 dikategorikan baik, sedangkan interval 99 dikategorikan sangat baik, dimana skor tersebut dikategorikan baik. Selanjutnya hasil analisis inferensial dilakukan dengan menggunakan aplikasi SPSS Versi 25. Hasil uji normalitas dan homogenitas diperoleh hasil data normal dan homogen. Sedangkan pengujian hipotesis dilakukan dengan menggunakan Paired Sample Pre-test Post-test dan diperoleh nilai signifikan lebih kecil dari 0,05 yaitu 0,000 dimana sig (2-tailed) < 0,05. Hal ini membuktikan Model Pembelajaran ICARE meningkatkan kemampuan berpikir kreatif siswa Kelas F SMAN 26 Bone.